2018
DOI: 10.1002/pon.4819
|View full text |Cite
|
Sign up to set email alerts
|

School performance of childhood cancer survivors in Korea: A multi‐institutional study on behalf of the Korean Society of Pediatric Hematology and Oncology

Abstract: We found that 20% to 25% of survivors experienced peer-related difficulties upon returning to school. Patients who return to school, especially high school, should be provided more educational support to overcome low academic achievement. Particular concern is needed to the patients with brain tumors, who are at risk for significant academic and social difficulties and therefore may require more intensive support in school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 30 publications
1
32
1
Order By: Relevance
“…Our results regarding physical activity and health grades show that PBTS had a lower average grade and failed to a higher extent than controls in this subject, which is in line with previous studies by Lähteenmäki et al ,7 Ahomäki et al 9 and Park et al 10. In our study, both girls and boys differed more from their controls in physical activity and health than in the other PRAEST subjects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results regarding physical activity and health grades show that PBTS had a lower average grade and failed to a higher extent than controls in this subject, which is in line with previous studies by Lähteenmäki et al ,7 Ahomäki et al 9 and Park et al 10. In our study, both girls and boys differed more from their controls in physical activity and health than in the other PRAEST subjects.…”
Section: Discussionsupporting
confidence: 92%
“…These studies have shown a greater risk of lower school grades for PBTS compared with controls. Only a few studies have included the subjects physical education7 9 10 and art/music,11 despite the fact that activities included in PRAEST subjects likely are valuable for essential skills and general well-being. For example, physical activity in the form of adventure-based training reduced fatigue and enhanced self-efficacy and quality of life among children treated for different types of cancer 12.…”
Section: Introductionmentioning
confidence: 99%
“…School absences were more frequent during the first school year of returning, for children in treatment or with brain tumours (Park et al, 2018) which were perceived negatively by parents (Hocking et al, 2018). If a formal plan to return to the school was not established, this appeared to lead to a more complicated and uncertain reintegration process (Chen et al, 2015;Pini et al, 2016;Rivero-Vergne et al, 2011;Tresman et al, 2016).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The main difficulties of continuing studying during treatment were described in three quantitative studies. These included high expectations from children or stakeholders, parental concerns, side effects or children's fears, hospitalizations and practicalities of accessing educational support (Lee et al, 2020;Park et al, 2018;Pini et al, 2013).…”
Section: Social Supportmentioning
confidence: 99%
“…A considerable minority report peer‐related difficulties and social isolation upon return to school, and this is particularly common among survivors of brain and central nervous system (CNS) tumours (Salley et al., 2014; Schulte et al., 2018). Survivors are more likely to underperform academically and again, survivors of CNS tumours are more susceptible due to poorer neurocognitive function (Barrera, Shaw, Speechley, Maunsell, & Pogany, 2005; Park et al., 2018; Zeltzer et al., 2009). Other vulnerable groups include those who are treated with cranial irradiation for other reasons (e.g.…”
Section: Introductionmentioning
confidence: 99%